Deciding treatment for miscarriage – experiences of women and healthcare professionals. Issue 2 (18th September 2014) - Linnet Olesen, Mette; Graungaard, Anette H.; Husted, Gitte R.
<x xml:space="preserve">Abstract</x> Introduction Women experiencing miscarriage are offered a choice of different treatments to terminate their wanted pregnancy at a time when they are often shocked and distressed. Women's and healthcare professionals' experiences of the decision‐making process are not well described. We aimed to gain insight into this process and the circumstances that may affect it. Method A qualitative study using a grounded theory approach. Data were obtained through semi‐structured interviews with six women who had chosen and completed either surgical, medical or expectant treatment for miscarriage and five healthcare professionals involved in the decision‐making at an emergency gynaecological department in Denmark. An inductive explorative method was chosen due to limited knowledge about the decision‐making process, and a theoretical perspective was not applied until the final analysis. Results Despite information and pretreatment counselling, choice of treatment was often determined by unspoken emotional considerations, including fear of seeing the foetus or fear of anaesthesia. These considerations were not discussed during the decision‐making process, which was a time when the women were under time pressure and experienced emotional distress. Healthcare professionals did not explore women's considerations for choosing a particular treatment and prioritised information differently. We found theory about coping and decision‐making in stressful situations useful in increasing our understanding of the women's reactions. In relation to theory about informed consent, our findings suggest that women need more understanding of the treatments before making a decision. This study is limited due to a small sample size, but it generates important findings that need to be examined in a larger sample. Conclusion Frequently, women did not use information provided about treatment pros and cons in their decision‐making process. Because of unspoken thoughts, and women's needs being unexplored by healthcare professionals, information did not target women's needs and their reasoning remained unapparent.